Public Service Quality in Banyuwangi District: A Study in Welfare Perspective - Hary Priyanto (Universitas Padjadjaran, 2024)
Administration Public service innovation must have a welfare impact on bureaucrats and citizens. Welfare for bureaucrats purpose to increase discipline and comply with the principles and objectives of public service. The habit of bureaucrats requesting something for the sake of accelerating stimulus in service is an example of how it is not easy for citizens to get their rights in public services, thus distancing citizens from aspects of welfare. This research aims to describe, analyze, and interpret welfare in the delivery of public services in Banyuwangi Regency. Researchers use a qualitative approach based on constructive and participatory patterns. Primary data was obtained from interviews, and secondary data was obtained from literature studies and government policies that were relevant to the research topic. Data analysis utilizes the Atlas Ti 8.4.23 application, 2018. The results obtained in this study: (1) Receiving awards is not commensurate with people's comfort in public services; (2) The Banyuwangi Regency Government needs to establish a policy so that additional grants to the welfare of the freelance worker bureaucrat do not violate existing policies; (3) Prosperity for citizens can be realized if service is fast, precise, non-discriminatory, and not connected to brokers; (4) It is necessary to internalize and implement systems and ways of working services from the perspective of the new administrative paradigm and Pancasila ideology.